Heart failure - Feldman, David S.; Mohacsi, Paul (Springer, 2019)
This textbook offers an up-to-date, user-friendly guide on the evaluation, diagnosis and treatment of this most important aspect of cardiovascular disease. Each chapter is dedicated to providing comprehensive coverage of every aspect of heart failure from cardiac signs and symptoms through imaging and the genetic basis for disease to surgery, interventions, treatment and preventative cardiology. Heart Failure provides the trainee and practising cardiologists, cardiac surgeon, vascular surgeon, diabetologist, cardiac radiologist and any physician who manages cardiac patients with extensive guidance on the diagnosis and management of a range of conditions related to heart failure. It is therefore, a critical resource for all cardiology practitioners, trainees’